2008
DOI: 10.1007/s12325-008-0037-7
|View full text |Cite
|
Sign up to set email alerts
|

Ischaemic preconditioning attenuates haemodynamic response and lipid peroxidation in lower-extremity surgery with unilateral pneumatic tourniquet application: A clinical pilot study

Abstract: Ischaemic preconditioning attenuates haemodynamic response and lipid peroxidation during lower-extremity surgery with unilateral tourniquet application.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 34 publications
0
16
0
Order By: Relevance
“…Data from humans are sparse. In a randomized trial of patients undergoing elective knee surgery under regional anesthesia, the oxygen and lactate contents in the femoral vein decreased significantly after local ischemic preconditioning using a tourniquet (Van et al, 2008). These authors did not measure flow to calculate VO 2 , but several studies have demonstrated, during ischemic arterial occlusion in the coronary, femoral or brachial arteries, that flow is increased during the period of reactive hyperemia, but returns to baseline values in 3 to 10 minutes (Ellins and Halcox, 2011;Engelke et al, 1996;Hayman et al, 2010;Krishnan et al, 2011;Olivecrona et al, 2004;Olivecrona et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Data from humans are sparse. In a randomized trial of patients undergoing elective knee surgery under regional anesthesia, the oxygen and lactate contents in the femoral vein decreased significantly after local ischemic preconditioning using a tourniquet (Van et al, 2008). These authors did not measure flow to calculate VO 2 , but several studies have demonstrated, during ischemic arterial occlusion in the coronary, femoral or brachial arteries, that flow is increased during the period of reactive hyperemia, but returns to baseline values in 3 to 10 minutes (Ellins and Halcox, 2011;Engelke et al, 1996;Hayman et al, 2010;Krishnan et al, 2011;Olivecrona et al, 2004;Olivecrona et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5]. However, reperfusion of the acutely ischemic lower limb can, in turn, induce reperfusion injury and cause remote vital organ dysfunctions [1,6,7].…”
Section: Introductionmentioning
confidence: 99%
“…One study used both anaesthetic and antioxidant intervention (propofol and N‐acetyl‐cysteine) (Table ). Three studies used ischaemic pre‐conditioning (Table ) and one study used both ischaemic pre‐conditioning and antioxidant intervention (N‐acetyl‐cysteine) (Table ).…”
Section: Resultsmentioning
confidence: 99%
“…Four studies used ischaemic pre‐conditioning; all used the same method, namely three cycles each of 5 min of ischaemia and 5 min reperfusion before final inflation of the tourniquet (Table ). One study used both ischaemic pre‐conditioning and N‐acetyl‐cysteine, but proved ischaemic pre‐conditioning to have better protective effects against ischaemia–reperfusion injury than N‐acetyl‐cysteine; it has therefore been listed in the ischaemic pre‐conditioning group (Table ).…”
Section: Resultsmentioning
confidence: 99%